PREPARATION OF COFE2O4, TIO2 AND ZNO NANOPARTICLES AND THEIR SURFACE MODIFICATION FOR STABLE NANOFLUIDS APPLICATION - ROSLAN, ANIS ARISA (2021)
Nanofluids can enhance the properties of the conventional base fluids due to their high surface area over volume ratio that makes them useful in many applications such as heat transfer, drug delivery and oil recovery. However, nanoparticles tend to agglomerate in base fluids due to the strong Van der Waals interactions, hindering the nanofluids from performing at their optimum level. The main objective of this work is to produce a homogeneous nanoparticles suspension in the base fluid by surface modification of nanoparticles. Three types of nanoparticles; cobalt ferrite (CoFe2O4), titanium dioxide (TiO2) and zinc oxide (ZnO) were synthesized via the hydrothermal method. The optimum temperature and duration for the hydrothermal growth of nanoparticles were determined by analyzing the effect of the synthesis parameter on the size and morphology of nanoparticles. The optimum temperature and duration for the hydrothermal growth of CoFe2O4, TiO2 and ZnO nanoparticles were found to be at 200°C for 5 hours, 120°C for 12 hours and 100°C for 2 hours, respectively. The synthesized nanoparticles were then used in the preparation of nanofluid. The stability of the nanofluids prepared via one-step and two-steps procedures were evaluated via physical observation of the formation of sedimentation over time. Polyethene glycol (PEG), poly (vinyl alcohol), polyvinylpyrrolidone and amino silane were used to study the effect of surface modification on the stability of the nanoparticles. The samples were characterized by using XRD, FESEM, TEM, FTIR, VSM and zeta potential to evaluate the crystalline phase and grain sizes, morphology, presence of functional groups, magnetic properties, and the stability of nanofluids. It is found that CoFe2O4-PVP based nanofluid exhibited the highest stability over 14 days with a zeta potential value of 62.2 mV, an increment of 59.1% compared to pure CoFe2O4 nanofluid. These findings provide a further understanding of the nanoparticles and nanofluids synthesis methods with surface modification alternative in contemplation of nanofluid stability enhancement.